Metformin extended‐release versus immediate‐release: An international, randomized, double‐blind, head‐to‐head trial in pharmacotherapy‐naïve patients with type 2 diabetes. Issue 2 (2nd October 2017) - Aggarwal, Naresh; Singla, Anuj; Mathieu, Chantal; Montanya, Eduard; Pfeiffer, Andreas F. H.; Johnsson, Eva; Zhao, June; Iqbal, Nayyar; Bailey, Clifford
Abstract : This international, randomized, double‐blind trial (NCT01864174) compared the efficacy and safety of metformin extended‐release (XR) and immediate‐release (IR) in patients with type 2 diabetes. After a 4‐week placebo lead‐in, pharmacotherapy‐naïve adults with glycated haemoglobin (HbA1c) at 7.0% to 9.2% were randomized (1:1) to receive once‐daily metformin XR 2000 mg or twice‐daily metformin IR 1000 mg for 24 weeks. The primary endpoint was change in HbA1c after 24 weeks. Secondary endpoints were change in fasting plasma glucose (FPG), mean daily glucose (MDG) and patients (%) with HbA1c <7.0% after 24 weeks. Overall, 539 patients were randomized (metformin XR, N = 268; metformin IR, N = 271). Adjusted mean changes in HbA1c, FPG, MDG and patients (%) with HbA1c <7.0% after 24 weeks were similar for XR and IR: −0.93% vs −0.96%; −21.1 vs −20.6 mg/dL (−1.2 vs −1.1 mmol/L); −24.7 vs −27.1 mg/dL (−1.4 vs −1.5 mmol/L); and 70.9% vs 72.0%, respectively. Adverse events were similar between groups and consistent with previous studies. Overall, metformin XR demonstrated efficacy and safety similar to that of metformin IR over 24 weeks, with the advantage of once‐daily dosing.